Open office y su influencia en el rendimiento académico a estudiantes del tercer año de bachillerato a, b, c de la Unidad Educativa Miguel Ángel Samaniego Jiménez parroquia la Unión, cantón Babahoyo, provincia los Ríos - Bustamante Arana, Yuly Maoly (2018)
The present research on Openoffice and its influence in the academic performance to students of the third year of baccalaureate the educational unit "Miguel Ángel Samaniego Jiménez" parish union, canton Babahoyo, province los ríos; It has been carried out with the purpose of providing teachers with new technological tools that will allow them to improve the academic level of the students, generating motivation for doing so and with it, a greater interest in studying. The research carried out a fieldwork where, through surveys, the causes and consequences of the problem that exists on the campus were determined, bibliographic sources were used in order to obtain theoretical supports that substantiate and give greater feasibility to the project. Finally, it is developed as a proposal the development of a didactic guide that will help the teacher to know and learn to use computer tools and thereby strengthen learning in their classrooms.